High specificity of engineered T cells with third generation CAR (CD28-4-1BB-CD3-ζ) based on biotin-bound monomeric streptavidin for potential tumor immunotherapy - Gallego-Valle, Jorge; Pérez-Fernández, Verónica Astrid; Rosales-Magallares, Jesús; Gil-Manso, Sergio; Castellá, María; Gonzalez-Navarro, Europa Azucena; Correa-Rocha, Rafael; Juan, Manel; Pion, Marjorie (Frontiers in Immunology, 2024)
Introduction Immunotherapy has revolutionized cancer treatment, and Chimeric Antigen Receptor T cell therapy (CAR-T) is a groundbreaking approach. Traditional second-generation CAR-T therapies have achieved remarkable success in hematological malignancies, but there is still room for improvement, particularly in developing new targeting strategies. To address this limitation, engineering T cells with multi-target universal CARs (UniCARs) based on monomeric streptavidin has emerged as a versatile approach in the field of anti-tumor immunotherapy. However, no studies have been conducted on the importance of the intracellular signaling domains of such CARs and their impact on efficiency and specificity Method Here, we developed second-generation and third-generation UniCARs based on an extracellular domain comprising an affinity-enhanced monomeric streptavidin, in addition to CD28 and 4-1BB co-stimulatory intracellular domains. These UniCAR structures rely on a biotinylated intermediary, such as an antibody, for recognizing target antigens. In co-culture assays, we performed a functional comparison between the third-generation UniCAR construct and two second-generation UniCAR variants, each incorporating either the CD28 or 4-1BB as co-stimulatory domain Results We observed that components in culture media could inhibit the binding of biotinylated antibodies to monomeric streptavidin-CARs, potentially compromising their efficacy. Furthermore, third-generation UniCAR-T cells showed robust cytolytic activity against cancer cell lines upon exposure to specific biotinylated antibodies like anti-CD19 and anti-CD20, underscoring their capability for multi-targeting. Importantly, when assessing engineered UniCAR-T cell activation upon encountering their target cells, third-generation UniCAR-T cells exhibited significantly enhanced specificity compared to second-generation CAR-T cells Discussion First, optimizing culture conditions would be essential before deploying UniCAR-T cells clinically. Moreover, we propose that third-generation UniCAR-T cells are excellent candidates for preclinical research due to their high specificity and multi-target anti-tumor cytotoxicity